Development of local wisdom-based synthetic analytical structural teaching materials for improving early reading students - Rahayu, Parmi; Sudiyanto, Sudiyanto; Kurniawan, Sandra Bayu (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The proficiency of early reading skill students is below expectations. Pupils need to read initially to obtain information from the media, help the learning process run well, and master learning activities for the next stage. This study aims to (1) examine expert validation of SAS teaching materials based on local wisdom, and (2) determine the effectiveness of SAS teaching materials based on local wisdom in improving students' early reading. The employed research method was Research and Development. The subjects of this study were grade 1 elementary school students in Boyolali Regency. The data collection techniques used were questionnaires, observations, and tests. The data analysis was descriptive qualitative, and quantitative in the form of a t-test and effect size. This study's results indicate that (1) SAS teaching materials based on local wisdom obtained validity from experts with an average of 85% in the very valid and very practical categories; (2) SAS method teaching materials based on local wisdom have been effective in the high category. The results of this study indicate that the SAS method teaching materials based on local wisdom that was developed were able to improve the initial reading skills of grade 1 elementary school students in Boyolali Regency.